Influence of the Shaper Design of Pneumohydraulic Impact Device on the Form and Duration of the Impact Impulse; Applied Mechanics and Materials; Vol. 756 : Mechanical Engineering, Automation and Control Systems (MEACS2014) - Angatkina O. O. (Modelling and Numerical Simulation, Algorithms and Mathematical Methods for Applied Problems, 2015)
Title screen